Microbial community structure and activity in trace element-contaminated soils phytomanaged by Gentle Remediation Options (GRO). (December 2017) - Touceda-González, M.; Prieto-Fernández, Á.; Renella, G.; Giagnoni, L.; Sessitsch, A.; Brader, G.; Kumpiene, J.; Dimitriou, I.; Eriksson, J.; Friesl-Hanl, W.; Galazka, R.; Janssen, J.; et al.
Abstract: Gentle remediation options (GRO) are based on the combined use of plants, associated microorganisms and soil amendments, which can potentially restore soil functions and quality. We studied the effects of three GRO (aided-phytostabilisation, in situ stabilisation and phytoexclusion, and aided-phytoextraction) on the soil microbial biomass and respiration, the activities of hydrolase enzymes involved in the biogeochemical cycles of C, N, P, and S, and bacterial community structure of trace element contaminated soils (TECS) from six field trials across Europe. Community structure was studied using denaturing gradient gel electrophoresis (DGGE) fingerprinting of Bacteria, α - and β - Proteobacteria, Actinobacteria and Streptomycetaceae, and sequencing of DGGE bands characteristic of specific treatments. The number of copies of genes involved in ammonia oxidation and denitrification were determined by qPCR. Phytomanagement increased soil microbial biomass at three sites and respiration at the Biogeco site (France). Enzyme activities were consistently higher in treated soils compared to untreated soils at the Biogeco site. At this site, microbial biomass increased from 696 to 2352 mg ATP kg −1 soil, respiration increased from 7.4 to 40.1 mg C-CO2 kg −1 soil d −1, and enzyme activities were 2–11-fold higher in treated soils compared to untreated soil. Phytomanagement induced shifts in the bacterial community structure at both, the total community and functional group levels, and generally increased the number of copies of genes involved in the N cycle ( nirK, nirS, nosZ, and amoA ). The influence of the main soil physico-chemical properties and trace element availability were assessed and eventual site-specific effects elucidated. Overall, our results demonstrate that phytomanagement of TECS influences soil biological activity in the long term. Graphical abstract: Highlights: Phytomanagement had a positive effect on soil microbial diversity and activity. Phytomanagement induced shifts in the bacterial community structure. Effects of phytomanagement were more pronounced after addition of soil amendments. Soil microbiological parameters are useful indicators of remediation progress. Abstract : Long-term phytomanagement has a positive effect on soil microbial diversity and activity and induced shifts in the bacterial community structure.